“Virtual Reality Box” Media in Improving the Knowledge of Brushing Elementary School Children - Saluna Deynilisa; Mujiyati; Abu Hamid (East Asian Journal of Multidisciplinary Research, 2022)
Virtual Reality Box is a technology that allows a person to simulate a real object using a smartphone. The purpose of the study was to find out that virtual reality boxes can increase the dental knowledge of elementary school children. Experimental method with pre-posttest design approach. The sample is 30 students. The results of the study can increase dental knowledge significantly, the posttest value (17.4) and the pretest value (7, 1), with statistical tests the results obtained P-value = 0.000 p value <0, statistically important differences in prior knowledge and after watching a dental knowledge video using a virtual reality box. In conclusion, virtual reality box media can improve knowledge.